2016
DOI: 10.1186/s12917-016-0930-2
|View full text |Cite
|
Sign up to set email alerts
|

Rope-based oral fluid sampling for early detection of classical swine fever in domestic pigs at group level

Abstract: BackgroundNon-invasive sampling techniques based on the analysis of oral fluid specimen have gained substantial importance in the field of swine herd management. Methodological advances have a focus on endemic viral diseases in commercial pig production. More recently, these approaches have been adapted to non-invasive sampling of wild boar for transboundary animal disease detection for which these effective population level sampling methods have not been available. In this study, a rope-in-a-bait based oral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Instead, ropes can be placed in the area frequented by wild boar, taking advantage of their natural chewing behavior. The ropes have been found to be attractive to wild boar, especially in areas with resources or supplementary food, facilitating OF collection [42]; (2) samples are easier to collect-therefore the metod is less stressful (welfare-friendly)-transport, and store; therefore, (3) this technique can be directly applied in field conditions, facilitating the implementation of surveillance and eradication measures [43].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, ropes can be placed in the area frequented by wild boar, taking advantage of their natural chewing behavior. The ropes have been found to be attractive to wild boar, especially in areas with resources or supplementary food, facilitating OF collection [42]; (2) samples are easier to collect-therefore the metod is less stressful (welfare-friendly)-transport, and store; therefore, (3) this technique can be directly applied in field conditions, facilitating the implementation of surveillance and eradication measures [43].…”
Section: Discussionmentioning
confidence: 99%
“…Sampling can be the bottleneck of swine fever diagnosis, especially in the case of wild boar, but also in remote areas. For this reason, alternative sampling strategies and sample matrices have been tested for CSF (often combined with African swine fever sampling) especially for wildlife specimens and under rural conditions [ 209 , 210 , 211 , 212 ]. However, most of them are not yet in routine use and need further validation.…”
Section: Diagnosismentioning
confidence: 99%
“…In free range animals, oral fluids have been collected using "samplers" consisting of short lengths (~10 cm) of rope embedded with a cereal-based bait matrix. Investigators have reported that the animals chewed the samplers, dropped them on the floor, and the next pig repeated the process, thereby providing an "aggregate" specimen [44,65]. Under experimental conditions, this approach provided for better CSFV or FMDV nucleic acids detection than oropharyngeal, nasal, or buccal swabs [44,65,88].…”
Section: Trouble-shooting Oral Fluid Collectionmentioning
confidence: 99%